Ответы и объяснения

2013-08-06T20:00:44+00:00
 \frac{16}{ \frac{S}{3} } +  \frac{S-16}{ \frac{S}{3}-1 }-3= \frac{1}{15}

 \frac{16*3}{ S } +  \frac{3*(S-16)}{ S-3 }= \frac{1}{15} +3

 \frac{16*3}{ S } + \frac{3*(S-16)}{ S-3 }= \frac{46}{15}

\frac{16*3*(S-3) + 3*S*(S-16)}{ S*(S-3) }= \frac{46}{15}

\frac{3*(16S-48 + S^{2} -16S)}{ S*(S-3) }= \frac{46}{15}

\frac{3*(S^{2} -48)}{ S*(S-3) }= \frac{46}{15}

45(S^{2} -48)=46 S(S-3) S(S-3) \neq 0

45S^{2} -48*45-46 S^{2}+46*3S=0

S^{2}- 46*3S +48*45=0

 \frac{D}{4} =  (-23*3)^{2} -48*45=9*( 23^{2}-48*5 ) = 9*289

S_{1}=23*3-3*17=3*6=18

S_{2}=23*3+3*17=3*40=120

Оба корня удовлетворяют условию S(S-3) \neq 0.
Ответ: 18; 120.